Pemanfaatan Pelayanan Kesehatan di Puskesmas - Basith, Ziana Aubi; Prameswari, Galuh Nita (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2020)
Number of patient visits in Puskesmas Gayamsari has decreased from 2015 to 2018. The scope of health service utilization in Puskesmas Gayamsari can be said low, because of the reach of patient visits in Puskesmas Gayamsari under the average patient visits in Puskesmas of Semarang City, that is 80%. The research objectives were to know the factors relate to the utilization of health services in Puskesmas Gayamsari. The type of research is an analytical observational with cross sectional design. The number of samples is 90 respondents selected with an accidental sampling using the chi-square test. Result shows that knowledge (p=0,000), attitude (p=0,009), individual assessment of the disease (p=0,000), facilities (p=0,000), doctor's service (p=0,016), accessibility (p=0,000), and ease of information (p=0,000) are related with the utilization of health services i Puskesmas gayamsari, while the level of education (p=0,379) is not related to the utilization. This research suggestion is to optimize the publication of the existence and benefits of Puskesmas Gayamsari as health service provider through mass media and soon.